Disjuntivismo: Principais Tipos E Críticas - Mota, Thiago Leite [UNIFESP] (2017)
Disjunctivism as a conception refuse the traditional philosophical idea that subjective indistinguishability between veridical and non-veridical perceptions (illusions and alucinations) gives as a result either the identity between the respective perceptual states, or the equivalency between the reasons offered for each one of them to sustain perceptual beliefs. Thus, the disjunctive conception of experience has implications about the nature of perception as well as scepticism about external world, a scepticism that bases itself precisely on the same kind of indistinguishability. On the present master thesis, one present how disjunctivism intends accomplish this double refusing task. On philosphy of perception, on the discussion about the nature of perception with defenders of causal theory of perception, Paul Snowdon argues, only instrumentaly, that veridical and non-veridical perceptions produce essentially distinct perceptual states, since they don't share a common element. Therefore, his version of disjunctivism is called metaphisical disjunctivism. On Theory of Knowledge, in the clash against the sceptics, Committed to the highest common factor conception, John McDowell in turn supports that veridical perceptions, contrary to mere appearances, yield indefeasible justification to perceptual beliefs by putting us in direct contact with the facts made manifest int the world, thereby can fundament a legitimate alegation of knowledge; so his conception gets the name of epistemological disjunctivism. From their respective formulations, both Snowdon and McDowell are confronted by reactions to their respective versions of disjunctivism. Thus, in this perspective, Snowdon debates, first, with William Child, about the possibility of compatibility between disjunctivism and causalism; then with Fish, about the nature of the dispute between disjunctivists and non-disjunctivists. On the other hand, McDowell debates initially with Tyler Burge as to which perceptual conception is better, anti-individualism or disjunctivism; next Crispin Wright and Duncan Pritchard discuss with McDowell the putative victory of disjunctivism over scepticism.